Catalytic hydropyrolysis of biomass using supported CoMo catalysts – Effect of metal loading and support acidity. (15th March 2020) - Stummann, Magnus Zingler; Elevera, Elaine; Hansen, Asger Baltzer; Hansen, Lars Pilsgaard; Beato, Pablo; Davidsen, Bente; Wiwel, Peter; Gabrielsen, Jostein; Jensen, Peter Arendt; Jensen, Anker Degn; Høj, Martin
Graphical abstract: Abstract: Catalytic hydropyrolysis of biomass to green fuels was performed using supported, sulfided CoMo catalysts. With MgAl2 O4 as support material the CoMo loading was varied between 4.1 and 12.0 wt% at constant Co/Mo atomic ratio of 0.3. Increasing the metal loading decreased the amount of oxygen in the condensed organic phase from 9.0 to 4.7 wt% on dry basis (db) and the condensable organic yield decreased from 25.2 to 22.7 wt% on dry ash free (daf) basis, corresponding to a decrease in the carbon recovery from 39 to 37%. Using zeolite H-ZSM-5 mixed with alumina as support with a CoMo loading of 4.1 wt%, the condensed organics contained only 5.2 to 6.1 wt% db oxygen. The condensable organic yield was between 23.9 and 24.4 wt% db, and the carbon recovery was 39–40%. Thus using an acidic support can remove the oxygen without decreasing the carbon recovery. The latter was ascribed to alkylation of the aromatics when the zeolite support was used. Elemental maps of the spent catalysts were obtained using STEM-EDS, showing that the CoMo phase was mainly located as monolayer MoS2 slab structures (>93%) on the support and indicated a high dispersion of cobalt, consistent with incorporation of Co into the MoS2 structure in the CoMoS phase. Potassium was observed on all the spent catalysts, indicating transfer of alkali metal from the biomass to the catalyst. Potassium may decrease the acidity of the catalyst over time, thus reducing the positive effect of using a more acidic support.